Large intra-abdominal dermoid cyst presenting as small bowel volvulus - Kumar, Suneed; Varty, Gurudutt (International Surgery Journal, 2017)
Intestinal obstruction is one of the commonest abdominal emergencies requiring surgical intervention. Among its numerous causes, volvulus of the small and large bowel plays a less common aetiological role. This is a rare case of a large intra-abdominal dermoid cyst causing small bowel volvulus and presenting as obstruction. 46-year-old male presented with four-day history suggestive of acute small bowel obstruction, with gross abdominal distension on examination. With minimal investigations, he was explored to reveal a large 10×8 cm sized cystic mass in lower abdomen, with two vascular pedicles causing twisting of small bowel and resultant obstruction. Surgical intervention included unwinding of viable bowel, dividing pedicles and excision of the mass. The cyst was found to contain pultaceous material with hair and solid components. Patient tolerated the procedure well and was asymptomatic on discharge and subsequent follow-ups. This case illustrates an uncommon cause of a common presentation; an uncommon location of a relatively common cystic swelling; and the diagnostic surprise that was encountered during the management, thereby reiterating the need for keen observation and clinical acumen while dealing with such cases.